Multicultural Based Islamic Education Innovation - Limayasa Ayu Oktarini; Hadi Saputra Panggabean (Hikmah, 2025)
Multicultural-based Islamic education innovation is a renewal of the learning process that emphasizes acceptance of the diversity of cultures, ethnicities, religions, and worldviews in society. This innovation includes not only the preparation of inclusive teaching materials, but also the application of interactive, reflective learning methods, and instilling the values of tolerance, justice, and peace according to Islamic teachings. This study aims to analyze the implementation of multicultural-based Islamic education innovations at SMA Negeri 1 Secanggang. The method used is a qualitative approach with in-depth interview techniques to obtain descriptive data. The results showed that the implementation of this innovation has been running quite well through the integration of Islamic values rahmatan lil-'alamin by Islamic education teachers in learning activities. However, the limited variety of methods, the narrow perspective of some students, and the negative influence of social media are the main challenges. Solutions include educative and persuasive approaches by teachers, collaboration with parents, as well as training and the use of creative learning media. Evaluation of effectiveness was conducted through learning outcomes, observation, and attitude assessment covering cognitive, affective, and psychomotor aspects.